(untitled) (Medical Forum Monthly, 2024)
Objective: To compare postoperative pain between standard vs mini percutaneous nephrolithotomy. Study Design: A Comparative Cross-Sectional Study Place and Duration of Study: This study was conducted at the Urology Department, Lady Reading Hospital, Peshawar from June 9th, 2022 to June 9th, 2023. Methods: A total of 140 patients with kidney stones (more than 10mm) were randomly allocated in two groups. Patients of Group A were subjected to mini PCNL while group B were subjected to standard PCNL. Follow-up was done to determine the intensity of pain on Visual Analogue Score (VAS). Results: In group A mean age was 36.3+8.5 years and in group B it was 38.9+10.1 years (p=0.096). Males in group A were 57.1% compared to 70% in group B (p=0.114). 14.5+3.7mm was mean size of stone in group A compared to 15.5+3.3mm in group B (p=0.071). The mean BMI of group A was 26.3+3.5kg/m2 compared to 26.2+3.3kg/m2 in group B (p=0.893). 14.3% in group A were diabetic compared to 17.1% in group B (p=0.642). 8.6% in group A were hypertensive compared to 11.4% in group B (p=0.573). 12.9% in group A were smokers compared to 24.3% in group B (p=0.082). On follow-up, the mean postoperative pain on the visual analogue scale in the group mPCNL group was 2.5+0.9 compared to 3.1+1.1 in the sPCNL group (p < 0.001). Conclusion: Mini PCNL is associated with less postoperative pain than standard PCNL. We recommend, taking into account the side effects of both procedures, more randomized control trails with larger samples.